Divergent synthesis of isoxazoles and 6H-1, 2-oxazines via hypervalent iodine-mediated intramolecular oxygenation of alkenes. (4th March 2022) - Chen, Yuhang; Zhang, Dingcheng; Sun, Mingze; Ding, Zhenhua
Abstract : A fluoro benziodoxole reagent was used for the intramolecular cyclization of β, γ-unsaturated oximes to form five- or six-membered ring products. Abstract : The divergent synthesis of isoxazoles and 6 H -1, 2-oxazines was realized using a hypervalent fluoroiodane reagent from β, γ-unsaturated oximes. The formation of a five- or six-membered ring is controlled by the substituents of the substrates combined with the reaction conditions. The reaction was performed under mild conditions and gave the products in moderate to good yields.